Effect of Fungicides and Herbicides against Rhizoctonia solani f. sp. sasakii Exner Causing Banded Leaf and Sheath Blight in maize (Zea mays L.) - Madhavi, M.; Reddy, P. Narayan; Manohar, K.; Kumari, Ch. Aruna (International Journal of Bio-resource and Stress Management, 2018)
Nine fungicides, one antibiotic and four herbicides including both systemic and non systemic were screened against Rhizoctonia solani f.sp. sasakii Exner (Thanatephorus sasakii (Shirai) Tu and Kimbrough causing Banded Leaf and Sheath Blight (BLSB) in maize. All the 27 isolates of R. solani from maize and one from rice were found to be highly sensitive to systemic fungicides propiconazole, hexaconazole, tebuconazole and carbendazim which showed cent % mycelial inhibition followed by new molecules i.e. cabriotop, metiram and pyraclostrobin at recommended and half the recommended concentrations. The isolate RS 28 from rice showed 78.88 and 90.00; 76.16 and 83.33% inhibition with respect to cabriotop and metiram at recommended and half the recommended concentrations, respectively. Among the non systemic fungicides mancozeb was relatively inhibitorier than thiram. Mancozeb at recommended concentration showed 72.22 % inhibition of mycelial growth in virulent isolates RS11 and RS12 from Khammam district. At recommended concentration validamycin, completely inhibited the radial growth of the isolates RS 4, RS 22, RS 24 and RS 27 while 80.00% inhibition in rice isolate. Among the herbicides tested, systemic herbicide pendimethalin was highly effective with per cent inhibition in all the isolates except for the isolate RS12 from Yellandu mandal of Khammam district at half the recommended concentration. While the remaining herbicides i.e. atazine, 2,4-D and paraquat exhibited differential reaction indicating variability among the isolates at both the concentrations tested. The rice isolate reacted in a similar way as that of maize isolates against different fungicides and herbicides tested.